Additive roll printing activated cold welding of 2D crystals and 1D nanowires layers for flexible transparent conductor and planer energy storage. (December 2016) - Nian, Qiong; Saei, Mojib; Hu, Yaowu; Deng, Biwei; Jin, Shengyu; Cheng, Gary J.
Abstract: Large scale integration of 2D crystals and metal nanowires (NWs) with low junction resistance has been a long time challenge for functional structures. Herein, roll to roll printing technique was utilized to directly produce graphene oxide (GO) nanoplatelets stack laminated with metal NWs. This 2D/1D laminated structure activates high pressure between AgNWs, enables localized fusion, and opens a new way to tackle with local nanojunction resistance. Molecular dynamic simulations reveal that this cold nanojoining originates from high localized pressure activated isolated metal atoms, which possess high mobility, flow over nanojunction and recrystallize to form nanojoints. Compared with bare AgNWs network, the GO laminated counterparts achieve excellent performance ( 17 Ω / sq, 93 % @ λ = 550 nm ), which enlightens optoelectronics applications. The cross nanowire junction resistance decrease is verified by classical percolation theory and experimental characterizations. Haze measurements show that the scattering is significantly reduced. Laminated structure has been engineered layer by layer to accomplish quasi-3D hybrid film, which demonstrated application in flexible supercapacitors with high specific capacitance of 109 F g −1 . This hybrid 2D/1D nanomaterial thin film also demonstrated excellent stability during cyclic foldability, stretchability, high temperature and oxidation tests. These investigations provide insight for layered manufacturing of 2D crystals/1D NWs structure and quasi-3D hybrid film for energy storage applications. Graphical abstract: